Investigation on Curing days of Concrete Waste Particle Reinforced Aluminium Matrix Composite - Misran, Anas Nashuha (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Particulate reinforced aluminium matrix composites (AMCs) are employed as major structural materials in aviation and automobile components. AMCs are materials that have ductile metallic alloys reinforced with hard particles, resulting in attractive properties. This is owing to its performance and distinctive qualities, which are enhanced by the reinforcement. Materials for this project included the aluminium alloy AA7075. The solid-state technology is used in this work to explore the influence of waste concrete as a reinforcing agent in aluminium matrix composites since it has significantly lower operation costs and energy than standard recycling by casting. The effects of concrete reinforcing on mechanical and physical characteristics were explored. Recycled aluminium chip AA7075 was reinforced with 2.5 %, 5%, 7.5 %, 10%, and 12.5% concrete with varied cure days of 7 and 28 days for each reinforcement composition. The current study identified density, apparent porosity, water absorption, micro-hardness, compression, and microstructure investigation of aluminium matrix composites. The finding reveals that range density of the specimen in g/cm³ between 2.3 and 2.6 only. For sample 1 which is 100% Aluminum shown that density gain until 2.5489 which is make the porosity get to 2.7648% and water absorption 1.7531%. The graph shown that the decreasing of percentages aluminum in specimen, the decreasing range different of density. The pattern is quite the same as the porosity graph which is related when the lower of porosity, the lower water absorption by specimen. Aluminum matrix composites reinforced with 5% concrete The maximum microhardness test result is 55.33 Hv after 7 curing days. The availability of reinforcing concrete has increased the hardness of aluminium matrix composites. . For the highest data get of the microhardness test which in the specimen with 87.5% aluminum and 12.5% of concrete 28 curing days. The composition of 95% aluminium with reinforced concrete has the greatest young’s modulus when compared to the others, with the reinforced 7 curing days being 13.24 MPa/m2 and the reinforced 28 curing days being 19.39.